2020
DOI: 10.1590/0103-8478cr20190196
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity of pea (Pisum sativum L.) varieties and the polyphenols, flavonoids, and antioxidant activity of their seeds

Abstract: Pea (Pisum sativum L.) is the fourth leading legume crop in the world, and its demand is increasing. In this study, the morphological characteristics (seed shape, seed surface, seed coat color, hilum color, cotyledon color, 100-seed weight and color values), total phenolic content (TPC), total flavonoid content (TFC), 2,2’-azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS) free radical scavenging capacity and ferric reducing antioxidant power (FRAP) of 75 pea cultivars were investigated. Results showed rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…G1 mousse contained over 10 mg/100 g more flavonoids than G2 and G3 mousses. This resulted from the very diverse composition of G1 mousse, which in addition to the base material (apples and spinach) contain rich in flavonoids: avocado, zucchini and green peas [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…G1 mousse contained over 10 mg/100 g more flavonoids than G2 and G3 mousses. This resulted from the very diverse composition of G1 mousse, which in addition to the base material (apples and spinach) contain rich in flavonoids: avocado, zucchini and green peas [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous active phytochemicals determined in pea-like flavonoids along with daidzein, genistein, asparaginase, apigenin,lectin, kaempferol and several phenolic compounds include catechin, coumaric acids, caffeic acids,vanillic acids, ferulic, pisatin, protocatechuic, proanthocyanidin, steroid phytohormone and tannins (Bello et al, 2018). Pea genotypes with different maturity level and seed coat colour showed prominent phenolics, total flavonoids along with high antioxidant activities (Devi et al, 2019;Zhao et al, 2020). Presence of techno-functional properties and phytochemical compositions in pea protein isolates could be used as value added ingredient in formulated foods (Pedrosa et al, 2020).…”
Section: Phytochemicals and Antioxidantsmentioning
confidence: 99%
“…Phenolic compounds are well studied for their antioxidant properties, and those of peas have been found to possess strong antioxidant activity . Zhao et al studied 75 different phenotypes of peas and found that the antioxidant activity was significantly correlated with seed coat color. Studies have also shown that seed coats/hulls contain the majority of the polyphenols in the seed. , Duenas et al reported that the hulls of two dark varieties of peas contained 25 phenolic compounds, mainly flavones, flavonols, tetrahydroxydihydrohalcone, and hydroxybenzoic acids.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive ROS is associated with many diseases, including hypertension, arteriosclerosis, and cancer . Dietary polyphenols have been shown to help maintain the balance between oxidants and antioxidants by suppressing the aforementioned oxidative stresses, , which involve glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), , and malondialdehyde (MDA) . Existing research has only focused on the intrinsic phenolics in raw or cooked pea-based foods and in vitro antioxidant activities; however, phenolic compounds may undergo extensive metabolism after ingestion, and the literature shows little correlation between in vitro and in vivo antioxidant activities .…”
Section: Introductionmentioning
confidence: 99%